Another reason : science and the imagination of modern India - Prakash, Gyan (Oxford University Press, 1999)
"Another Reason is a bold and innovative study of the intimate relationship between science, colonialism, and the modern nation. Gyan Prakash, one of the most influential historians of India writing today, explores in fresh and unexpected ways the complexities, contradictions, and profound importance of this relationship in the history of the subcontinent.